The association between parents' stress and parental feeding practices and feeding styles: Systematic review and meta‐analysis of observational studies - Dina Almaatani; Andreea Zurbau; Farnaz Khoshnevisan; Robert H. J. Bandsma; Tauseef A. Khan; John L. Sievenpiper; Meta Van Den Heuvel (Wiley, 2023)
Abstract In the extended UNICEF framework of early childhood nutrition, parents' stress is associated with parental feeding style. However, no comprehensive review has examined the association between parents' stress and feeding styles and practices. The objective of our review was to synthesise the current literature examining the association between parents' stress and their feeding practices and/or styles, among parents of children ≤ 5 years old. We searched; MEDLINE, EMBASE, PSYCHINFO and CINAHL from 2019 to 2021. Two investigators independently extracted relevant data and assessed the study quality and the certainty of evidence. Data were pooled using generic inverse variance with fixed effects (<5 comparisons) or random effects (≥5 comparisons) and expressed as correlation coefficients with 95% confidence intervals (CI). Between study heterogeneity was assessed using Cochran's Q and quantified with I2. We identified 6 longitudinal and 11 cross‐sectional studies, of which 4 studies provided sufficient data to be pooled. A very small correlation between general stress and restrictive feeding practices was observed (r = 0.06 [95% CI: 0.01−0.12]; no substantial heterogeneity (I2 = 0.00%, PQ < 0.85, very low certainty). No correlation between general stress and feeding pressure was identified (r = 0.06 [95% CI: −0.02 to 0.15]). Results showed that both general and parenting stress were associated with suboptimal breastfeeding practices and unresponsive feeding styles. Conclusion: This study demonstrated a low‐to‐moderate quality of literature for the inclusion of parents' stress in the extended UNICEF care model of child nutrition. Future research needs to explore this relationship longitudinally and in ethnic diverse populations to inform tailored interventions that promote responsive feeding practices.